“Kahoot!” Gamification, Innovation and Digital Literacy as Teaching Media in Improving EFL Students’ Vocabulary - Nupus, Hayati; Qomaruzzaman, Maman (PROJECT (Professional Journal of English Education), 2026)
This study conducted to find out the effectiveness of using Kahoot as a teaching and learning media in improving students' English vocabulary. This study used quantitative approach, pre-test and post-test conducted to determine whether the students differed before and after the implementation of kahoot as learning media. The research subjects consisted of students who participated in English learning using Kahoot as an interactive quiz medium. vocabulary test conducted to collect the data before and after implementation. The results of the research indicated that there is a significant improvement of students' vocabulary mastery after using kahoot as learning media. This is due to the interactive, competitive, and fun nature of Kahoot, which is able to increase student motivation and creativity in the teaching and learning activity. In addition, the use of game-based technology helps students remember new vocabulary more effectively through repetition and direct feedback. Thus, Kahoot can be an alternative, innovative and effective learning medium in improving students' English vocabulary skills. This research is expected to gain more development and contribution of more interesting and technology-based English learning methods.